PR Management of BP Oil Spill on Gulf of Mexico-A Strategic Communication Approach - Sakyi, Kwesi Atta (Advances in Social Sciences Research Journal, 2019)
Disaster management is cardinal in supply chain management as well as in strategic communication and public relations. This paper examines the BP Oil spill on the Gulf of Mexico in 2010 and explores how rapidly growing social media comes in handy in getting suitable communication to targeted publics. This paper makes the case that traditional news media has become obsolete as it is an outlet for a select elite who massage the content of news. This paper examines the context of the primary and secondary messages which were sent out during the whole episode as well as how best the communication should have been handled strategically. The paper relies on secondary sources to review the case and ends by making recommendations.